COVID-19: Trade restrictions are worst possible response to safeguard food security - Glauber, Joseph W.; Laborde Debucquet, David; Martin, Will; Vos, Rob (International Food Policy Research Institute, 2020)
As COVID-19 spreads around the globe, fears of a deep global recession are mounting. Some also fear that food supplies may start running short, especially if supply chains are disrupted. Others fear that agricultural production may be disrupted by containment measures that restrict workers fromharvesting and handling crops. While we should take these concerns seriously — especially for fruits and vegetables, which have complex supply chains, or foods sold primarily through restaurants — they should not be overstated either, especially not for basic staples such as rice, wheat, and maize. Global markets are well supplied, stocks are healthy, production of key staples is unlikely to be disrupted, and prices have remained relatively stable. Trade is allowing production to move from areas of surplus to areas of shortage, avoiding the drastic shortages and food insecurity associated with reliance only on local production.